Effect of annual fire on tallgrass prairie legumes - Towne, G.; Knapp, A.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Total legume density was significantly higher in annually burned prairie (8.0 stems/m2) than in unburned prairie (3.0 stems/ m2). Densities of six species were higher (P<.05) in burned than in unburned prairie, whereas only one legume species decreased from annual fire. Total legume biomass did not differ between burned (11.3 g/m2) and unburned prairie (10.5 g/m2). Most legume species either are favored by fire or are fire tolerant, and their persistence in annually burned grassland suggests that they may play an important role in the nitrogen budget of tallgrass prairie.
Keywords: Beef; Fire; Forage; Legumes; Tallgrass prairie